A charter granted to the Company of Royal Adventurers of England Trading into Africa - Great Britain; Charles II; Royal African Company; British Library; Adam Matthew Digital (Adam Matthew Digital, 1672)
Ms. copy of the Charter granted by Charles II in 1672, to promote British trade in Africa, 1672